Prevention of Wrinkling in Shrink Flanging of Ultra-High Strength Steel Sheets Using Gradually Contacting Punch - Zamzuri, Hamedon; Mori, Ken-ichiro; Abe, Yohei; Watanabe, Saharu (2014)
To prevent the occurrence of wrinkling in the shrink flanging of ultra-high strength steel sheets, a gradually contacting punch was developed. Compressive stress around the convex corner of the sheet in shrink flanging was reduced by gradually bending the edge from the center to the outside of the sheet using the gradually contacting punch. Compressive strain around the convex corner edge decreased as the contact angle of the punch increased. Although a small camber occurred on the upper surface of the flanged sheet using the conventional flat bottom punch, the camber was large using the gradually contacting punch because of the gradual bending. The limiting flange height of the flanged sheet without wrinkling showed an increase of 26% for the 980 MPa grade ultra-high strength steel sheet.